Multi-scale spectral analysis in hydrology : from theory to practice - S, Adarsh; Reddy, M Janga (Boca Raton, FL : CRC PRESS, 2021)
Accurate prediction of hydrological variables is essential for efficient water resources planning and management. Proper understanding of the characteristics of the time series may help in improving the simulation and forecasting accuracy of hydrological variables. This book presents a detailed description and application of multiscale time-frequency characterization tool for the spectral analysis of hydrological time series. It presents spectral analysis methods for hydrological applications through a wide variety of illustrative case studies including Wavelet transforms, Hilbert Huang Transform and their extensions.
OCLC-licensed vendor bibliographic record.
Keywords: Hydrologic cycle; MATHEMATICS / Number Systems; SCIENCE / Environmental Science; TECHNOLOGY / Engineering / Civil